Experimental analysis of multistatic wind turbine radar clutter statistics. Issue 3 (1st February 2016) - Fioranelli, F.; Ritchie, M.; Balleri, A.; Griffiths, H.
Abstract : This Letter presents preliminary results of the analysis of amplitude statistics of wind turbine clutter as extracted from multistatic radar data. It is shown that the T ‐location‐scale distribution provides good fitting of the experimental data, and that there are combinations of bistatic angle and polarisations where the bistatic clutter has more favourable statistics for target detection than the simultaneous monostatic clutter.